Evaluation of the Effectiveness of Carbon Emission Reduction Policies in Banjarnegara: Approach Economics and Regulation - Rohmah, Feni Nur; Prastica, Ika Yuliana; Setyawan, M. Arif; Hartiyah, Sri (Proceedings Series on Social Sciences & Humanities, 2025)
This research aims to evaluate the effectiveness of carbon emission reduction policies in Banjarnegara Regency, Central Java. Includes the implementation of a Carbon Tax, Intensive Renewable Energy, and Emissions Regulations in the Transportation Sector. With the main focus being on the Agricultural, Small Industry and Transportation Sectors which are the main sources of carbon emissions in the Banjarnegara Region. This research uses quantitative methods to analyze the impact of economic and regulatory policies on reducing carbon emissions in areas dominated by agricultural activities and traditional energy use. Data was obtained from relevant agencies and field surveys, and analyzed using linear regression and correlation to see the relationship between implemented policies and changes in emission levels from 2018 - 2023.